Psychological reflection of archetypal ideas (Yong) in the poems of modernist Kurdish poets (not selected poets) - Masoume GomeJamour; hojatolah ghmoniri; parvin rezaei (مجله علوم روانشناختی)
Background: Archetypal ideas originate from the collective unconscious of humans and because they are embedded in the nature and institution of humans, and in everything that is the product of human thought, taste and feeling, they appear. From the point of view of the schema, excesses in the formation of psychological needs cause the formation of schemas. Literary works, including poetry, due to the fact that it comes from the human soul, are connected with archetypal ideas and poetry is considered as a collective unconscious medium of humans. Aims: The purpose of the current research is the psychological reflection of archetypal ideas (Yang) in the poems of modernist Kurdish poets (not selected poets). Methods: In this regard, in this article written in a library method, archetypal ideas in the poems of several modernist Kurdish poets have been investigated. Results: The results of the research show that these poets have used archetypal images and images abundantly in their poetry. Of course, this has several reasons; One is that most of these poets are in conflict with the manifestations of civilization and urbanization, and they present the elements of nature and countryside as an unattainable dream in their poetry, and this directly causes the elements of nature and archetypal images to enter their poetry. The second reason is that most of these poets have a political and social orientation and themes such as freedom and homeland are considered central themes of their poems, but due to the limitations, they are forced to turn to symbolic and ambiguous language. Conclusion: These poets turn to similes and metaphors to express the themes of freedom and homeland, and this causes natural and archetypal elements to enter their poems.